Chemical analysis of cuticular compounds in Alphitobius diaperinus via Chemical Ionization - Mass Spectrometry - Guimas Mazzetti, Aldo Gustavo (2021)
Alphitobius diaperinus represents a serious plague problem for the poultry industry. The possibility of utilizing biotraps for control of A. diaperinus is promising, but still merits more research, in particular with regards to the identification of compounds for their possible use in biotraps for A. diaperinus. Herein, data from a GC-MS experiment carried out on a cuticular extract of A. diaperinus is statistically analyzed, preparing the data for analysis and carrying out data filtration by a one-way ANOVA (p-value < 0.01) and finally data visualization by PCA. Three compounds of interest are successfully identified: 2-methyl-1,4-benqouinone, 2-ethyl-1,4-benzoquinone and 2-ethyl-1,4-hydroquinone.